Dietary essential oils improve feed efficiency and hepatic antioxidant content of broiler chickens. (10th July 2018) - Pirgozliev, V.; Mansbridge, S. C.; Rose, S. P.; Mackenzie, A. M.; Beccaccia, A.; Karadas, F.; Ivanova, S. G.; Staykova, G. P.; Oluwatosin, O. O.; Bravo, D.
Abstract : The aim of this study was to test the hypothesis of an improved growth, dietary nutrient availability and overall health of broiler chickens reared on recycled litter when fed a standardised combination of essential oils (EO; carvacrol, cinnamaldehyde and capsicum oleoresin). To assess the effect of dietary treatments, feed intake, weight gain, feed efficiency, availability of dietary nutrients and energy, villus morphometry, excreta sialic acid concentration, hepatic antioxidants and serum amyloid A (SAA) when fed to broiler chickens were evaluated. Counts of Eimeria spp. oocysts were also determined in excreta samples. Four experimental diets were offered, including two basal control diets based on either wheat or maize that contained 215 g CP/kg and 12.13 MJ/kg metabolisable energy and another two diets using the basal control diets supplemented with the EO combination at 100 mg/kg diet. Each diet was fed to eight floor pens, containing two birds each, following randomisation. Birds fed the EO-supplemented diets had an improved ( P <0.05) feed conversion ratio (FCR). Birds fed maize-based diet had an improved daily weight gain and FCR ( P <0.05) compared with wheat-fed birds. Wheat-based diet tended ( P =0.056) to have greater N-corrected apparent metabolisable energy and had greater fat retention coefficient ( P <0.05) compared with maize-based diets. No differences ( P >0.05) were observed in villus morphometry, sialic acid secretion, number of oocysts and SAA. Feeding the EO improved ( P <0.05) the retention of dietary Ca and Na. Compared with maize, feeding wheat-based diets improved the retention coefficients for Ca, P and Na ( P <0.05). Feeding dietary EO improved ( P <0.05) the concentrations of the hepatic antioxidants, including carotene, coenzyme Q10 and total vitamin E. The hepatic concentration of carotene of the maize-fed birds was 55.6% greater ( P <0.05) compared with the wheat-fed birds. These results demonstrated that the addition of a standardised combination of EO in wheat- and maize-based diets provided benefits in terms of feed efficiency, mineral retention and antioxidant status of the birds when reared on recycled litter.